Dietary bamboo vinegar powder supplementation mitigates the adverse effects of a high-starch diet on growth performance, liver health, and glucose-lipid metabolism in largemouth bass (Micropterus salmoides) - Weibin Lai; Zhangyi Xiao; Ran Yu; Linyi Li; Wenqian Chen; Yuan Gao; Manqi Yang; Liangliang Zhang; Liming Lu; Jianchun Jiang (Frontiers in Marine Science, 2026)
This study explored the potential of bamboo vinegar powder (BVP) to mitigate hepatic injury and metabolic disturbance induced by a high-starch diet in largemouth bass ( Micropterus salmoides ). Fish were distributed into three groups (with three replicates per group) and fed for 56 days with a basal diet (BD), a high-starch diet (CSD), and the BVP-supplemented diet (CSDB, added 2.0 g/kg BVP to the CSD diet), respectively. After the feeding trial, fish in the CSD group exhibited a significant decrease in weight gain rate (WGR) and an increased hepatosomatic index (HSI) ( P < 0.05). Concurrently, hepatic glucose and lipid metabolism of fish in the CSD group were suppressed, leading to the accumulation of hepatic lipids and glycogen, along with histopathological manifestations such as hepatic vacuolation and nuclear shift. Furthermore, immune competence and hepatic antioxidant status were also compromised. However, relative to the CSD group, fish in the CSDB group demonstrated significant improvements in growth performance, immune function, and liver injury. Furthermore, BVP upregulated the expression of nuclear factor erythroid 2-related factor 2 ( nrf2 , a key regulator of antioxidant defense) and downregulated the nuclear factor kappa B ( nf - κb , a central transcription factor in inflammation) ( P < 0.05). More importantly, BVP might improve the metabolism of hepatic glucose and lipid in fish, by suppressing gluconeogenesis and promoting glycolysis to optimize glucose metabolism, as well as by inhibiting lipogenesis and promoting both lipid transport and catabolism to enhance lipid metabolism. Notably, dietary BVP supplementation significantly altered hepatic metabolite profiles, affecting pathways such as alpha-linolenic acid and arachidonic acid metabolism, and increasing the levels of several lipid metabolites, including docosahexaenoic acid and phosphatidylethanolamine species, compared to the CSD group ( P < 0.05). Collectively, these results demonstrated that BVP improved growth performance, liver health, and glucose-lipid metabolism in largemouth bass fed a high-starch diet.